PENGARUH LATIHAN IKAN DAN KEPITING TERHADAP KECEPATAN MENGGIRING BOLA PADA SSB RUMBAI PRATAMA - Wiranata, Agus; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: based on observations by researchers from the Rumbai Pratama SSB, there are still many players who fail to feed herding. Failures that often occur when dribbling as opponents easily grab the ball, when dribbling the ball is far from the feet and very slow, this is because the dribbling technique is very lacking for players, and researchers want to give fishing and crab training to the speed of hats . So that players can perform and play much better in the future and the most important thing after research is to see if the speed of leading players in football matches is increasing, so that they can match the opponent's game and achieve maximum results in the future. The design of this research is a pre-test post test, a group design that starts with a Pree dribble test. The sample then received a fish and crab training program for 16 meetings. The post-dribble test is then completed. Based on the results of the pre-test and post-test data analysis, the t-test produced a T-count of 6.00 and Ttable 1.753. It means that Tcount> Ttable can be closed as follows: There is a significant effect of the training of fish and crabs (X) on the speed of herding (Y) in the SSB Rumbai Pratama.Key Words: Fish and crab exercises, Ball Dribbling Speed